1996
DOI: 10.1006/dbio.1996.0240
|View full text |Cite
|
Sign up to set email alerts
|

The Embryonic Central Nervous System Lineages ofDrosophila melanogaster

Abstract: Central nervous system development in Drosophila starts with the delamination from the neuroectoderm of about 30 neuroblasts (NBs) per hemisegment. Understanding the mechanisms leading to the specification of the individual NBs and their progeny requires the identification of their lineages. Here we describe 17 embryonic NB lineages derived from the ventral half of the neuroectoderm and we assign these lineages to identified medial and intermediate NBs. The lineages are composed of interneurons (NB 1-2, NB 2-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(152 citation statements)
references
References 3 publications
4
145
3
Order By: Relevance
“…As the insect NB 1-1 (Doe 1992;, b1hn of Orchestia is the first NB in the segment close to the midline lying behind two rows of en positive NBs (figure 5a,g). A second candidate was the NB 4-2 of Drosophila (figure 5g), again based on its position and its characteristic offspring, the pioneer neuron RP2 (Bossing et al 1996;Landgraf et al 1997;Schmid et al 1999; figure 6b). We found that the NB d1hnin of Orchestia shares the medial position in the anteroposterior axis (figure 5a) and among others the production of the well-identifiable pioneer neuron RP2 (figure 6a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the insect NB 1-1 (Doe 1992;, b1hn of Orchestia is the first NB in the segment close to the midline lying behind two rows of en positive NBs (figure 5a,g). A second candidate was the NB 4-2 of Drosophila (figure 5g), again based on its position and its characteristic offspring, the pioneer neuron RP2 (Bossing et al 1996;Landgraf et al 1997;Schmid et al 1999; figure 6b). We found that the NB d1hnin of Orchestia shares the medial position in the anteroposterior axis (figure 5a) and among others the production of the well-identifiable pioneer neuron RP2 (figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…It lies in the dorsalmost layer of the CNS between ac and pc (white star) and sends an axon anteriorly in the connective and into the intersegmental nerve (white arrowheads). (b) Neuroblast 4-2 of Drosophila (after Bossing et al 1996). The motoneuron RP2 lies in the dorsalmost layer of the ganglion and sends an axon into the intersegmental nerve (red open arrowheads).…”
Section: Resultsmentioning
confidence: 99%
“…Glioblasts, on the other hand, produce pure glial lineages (Bossing et al 1996;Schmid et al 1997;Schmid et al 1999). In some neuroglioblast lineages, the bifurcation between the neuronal and the glial lineages occurs in the primary division to produce a neuronal and a glial precursor (figure 4a; Akiyama-Oda et al 1999; Bernardoni et al 1999).…”
Section: Neurogenesis In Drosophila (A) Neuroblast Formation: Notch Smentioning
confidence: 99%
“…Each of the first five GMCs (GMC1-5) that NB7-1 produces divides to produce a motor neuron (named U1-U5 with birth order) and a sibling. Each of the U1-U5 motor neurons can be identified by their position and their unique expression of molecular markers ( Bossing et al 1996;Schmid et al 1999;Pearson & Doe 2003).…”
Section: Specification Of Temporal Identitymentioning
confidence: 99%
“…In several representatives of this group of organisms all neuroblasts in the thoracic ganglia are individually identified concerning their position and the lineage which they generate and are well characterized on the molecular level (e.g. Doe 1992; Doe and Technau 1993;Broadus et al 1995;Bossing et al 1996;Schmidt et al 1997; see also the hyper neuroblast map at http://www.neuro.uoregon. edu/doelab/nbintro.html).…”
Section: Introductionmentioning
confidence: 99%